2020
DOI: 10.1093/intqhc/mzaa018
|View full text |Cite
|
Sign up to set email alerts
|

Implementing and measuring person-centredness using an APP for knowledge transfer: the iMPAKT app

Abstract: Objective The aim of the study was to evaluate a technological solution in the form of an App to implement and measure person-centredness in nursing. The focus was to enhance the knowledge transfer of a set of person-centred key performance indicators and the corresponding measurement framework used to inform improvements in the experience of care. Design The study used an evaluation approach derived from the work of the Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 9 publications
2
19
0
Order By: Relevance
“…Findings also reinforced the potential for real‐time reporting using the iMPAKT App, despite the technological challenges that were experienced during the implementation phase. Furthermore, the findings reflected the outcomes from previous implementation studies, highlighting the celebratory nature of implementing the KPIs as a process that can evidence the positive contribution of nursing and the potential to develop practice (McCance et al, 2015; McCance et al., 2020).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Findings also reinforced the potential for real‐time reporting using the iMPAKT App, despite the technological challenges that were experienced during the implementation phase. Furthermore, the findings reflected the outcomes from previous implementation studies, highlighting the celebratory nature of implementing the KPIs as a process that can evidence the positive contribution of nursing and the potential to develop practice (McCance et al, 2015; McCance et al., 2020).…”
Section: Discussionsupporting
confidence: 62%
“…The evolution of this research led to a further study to develop and test the feasibility of a technological solution to facilitate the collection of data using the measurement tools. It demonstrated that the App made information more accessible, was captured in real time and used to improve the experience of care (McCance et al., 2020). The person‐centred nursing KPIs have largely been tested within acute care settings.…”
Section: Introductionmentioning
confidence: 99%
“…Our results confirm the findings of McCance et al [42] that analysed the eight KPIs clustered within the person-centered processes domain of the framework, and these KPIs were related to patient satisfaction, confidence, and implication in the decision-making process about his/her care.…”
Section: Resultssupporting
confidence: 90%
“…Initially, the KPIs were tested using a paper‐based format. However, the findings of a feasibility study using a mobile health app to capture the KPI data (McCance, Lynch, et al, 2020) indicated that an app assisted data collection, collation and reporting. The app developed for this purpose is called iMPAKT (Implementing and Measuring Person‐centredness using an App for Knowledge Transfer) and captures quantitative and qualitative person‐centred data relating to the KPIs to evidence the patient experience.…”
Section: Introductionmentioning
confidence: 99%
“…The study reported by McCance, Lynch, et al (2020) found that using the app to capture data improved efficiency in the collection and reporting of results and the development of practice improvements. The findings reported in this paper are a follow on from the feasibility study reported by McCance, Lynch, et al (2020). The purpose of this study was to explore over time, how nurses and midwives engage with person‐centred data pertaining to the patient perspective collected via a mobile health (mHealth) app to inform person‐centred quality and safety improvements.…”
Section: Introductionmentioning
confidence: 99%